Analisis Pengaruh Rasio Keuangan Dalam Prediksi Financial Distress Pada Perusahaan Manufaktur Yang Terdaftar Di Bei Pada Tahun 2010-2013 - Kumalaningrum, Bimbi, Dra. Rina Trisnawati, Ak, M.Si Ph.D (2015)
Financial distress or financial hardship is a condition experienced by the company prior to the bankruptcy or liquidation. Financial distress is able to predict with a variety of ways, one of which is by using financial ratios. The purpose of this study was to analyze the influence of financial ratios, the current ratio (CR), return on assets (ROA), debt to total assets (DAT), total asset turnover (TAT), and price earnings ratio (PER) of the prediction of financial distress. This research is an empirical study using secondary data. The object of this research is manufacturing companies listed on the Stock Exchange during the study period 2010-2013. The sample used in this study as many as 158 companies and 20 non financial distress financial distress company, selected by purposive sampling. Statistical method used is logistic regression. This research results show that: the current ratio, return on assets, total asset turnover and price earnings ratio does not affect the prediction of financial distress. While debt to total assets affect the prediction of financial distress. Keywords: current ratio, return on assets, debt to total assets, total asset turnover, the price earnings ratio, danfinancial distress.